Occupational Health Hazards and Problems among Sawmill Workers in Benin Metropolis, Edo State - Adesua, Agbonifoh Julia; Margaret, Onobumeh; Efe, Omoregie Rose (NIU Journal of Social Sciences; Vol 6 No 3 (2020): KIU Journal of Social Sciences, Vol. 6 No. 3, September 2020, 2020)
The purpose of this study was to examine the occupational health hazards of sawmill workers in Benin metropolis.  Four research questions, relating to occupational health hazards and problems of sawmill workers were raised and answered.  The descriptive survey designed was adopted for the study. The stratified random sampling was used to select 100 respondents for the study. The research instrument (questionnaire) was validated by three experts in the Department of Health, Safety and Environmental Education, while  test re-test method of reliability was used to determine its correlation co-efficient.  The data collected was analyzed using descriptive statistics of mean and standard deviation. Findings revealed that sawmill workers are confronted with numerous health hazards associated with sawmilling, and that they adhere to safety regulations. It was therefore recommended that sawmill owners should as a matter of urgency make provision for the unavailable personal protective equipment to prevent workers from contracting diseases related to sawmilling.  It was expected that the outcome of the study would be useful in preventing diseases associated with saw milling and also to ensure that there is improvement in adherence to safety regulation by the sawmill workers. Keywords:  Occupational  Health,  Hazards, Sawmill Workers